2021
DOI: 10.48550/arxiv.2110.02629
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deep Reinforcement Learning for Solving the Heterogeneous Capacitated Vehicle Routing Problem

Jingwen Li,
Yining Ma,
Ruize Gao
et al.

Abstract: Existing deep reinforcement learning (DRL) based methods for solving the capacitated vehicle routing problem (CVRP) intrinsically cope with homogeneous vehicle fleet, in which the fleet is assumed as repetitions of a single vehicle. Hence, their key to construct a solution solely lies in the selection of the next node (customer) to visit excluding the selection of vehicle. However, vehicles in real-world scenarios are likely to be heterogeneous with different characteristics that affect their capacity (or trav… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…Additionally, Bono et al [15] proposed a modified Transformer model to handle the dynamic and stochastic VRPs (DS-VRPs) by using online measurements of the environment to online select the next vehicle via a vehicle-customer intersection module. More recently, Li et al [25] improved the AM to solve the Heterogeneous Capacitated VRP (HCVRP). Li et al [26] proposed the attention-dynamic model to solve the covering salesman problem (CSP).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Bono et al [15] proposed a modified Transformer model to handle the dynamic and stochastic VRPs (DS-VRPs) by using online measurements of the environment to online select the next vehicle via a vehicle-customer intersection module. More recently, Li et al [25] improved the AM to solve the Heterogeneous Capacitated VRP (HCVRP). Li et al [26] proposed the attention-dynamic model to solve the covering salesman problem (CSP).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, Kool et al [3] showed that a greedy rollout baseline yields better results than a (learned) critic baseline. Many subsequent works, including [6,[25][26][27], and [7], used the greedy rollout baseline. Although the greedy rollout baseline is effective, it requires an additional forward-pass of the model, increasing the computational load on the device.…”
Section: Literature Reviewmentioning
confidence: 99%